Compartmentalized phosphodiesterase-2 activity blunts beta-adrenergic cardiac inotropy via an NO/cGMP-dependent pathway. - Mongillo, M; Tocchetti, C; Terrin, A; Lissandron, V; Cheung, Y; Dostmann, W; Pozzan, T; Kass, D; Paolocci, N; Houslay, MD; Zaccolo, M (2006)
beta-Adrenergic signaling via cAMP generation and PKA activation mediates the positive inotropic effect of catecholamines on heart cells. Given the large diversity of protein kinase A targets within cardiac cells, a precisely regulated and confined activity of such signaling pathway is essential for specificity of response. Phosphodiesterases (PDEs) are the only route for degrading cAMP and are thus poised to regulate intracellular cAMP gradients. Their spatial confinement to discrete compartments and functional coupling to individual receptors provides an efficient way to control local [cAMP]i in a stimulus-specific manner. By performing real-time imaging of cyclic nucleotides in living ventriculocytes we identify a prominent role of PDE2 in selectively shaping the cAMP response to catecholamines via a pathway involving beta3-adrenergic receptors, NO generation and cGMP production. In cardiac myocytes, PDE2, being tightly coupled to the pool of adenylyl cyclases activated by beta-adrenergic receptor stimulation, coordinates cGMP and cAMP signaling in a novel feedback control loop of the beta-adrenergic pathway. In this, activation of beta3-adrenergic receptors counteracts cAMP generation obtained via stimulation of beta1/beta2-adrenoceptors. Our study illustrates the key role of compartmentalized PDE2 in the control of catecholamine-generated cAMP and furthers our understanding of localized cAMP signaling.